Writen argumentation abilities in Peruvian second Middle school students (Revista Peruana de Investigación Educativa, 2024)
The capacity to argue about controversial issues is crucial to build a democratic society. Each person has different points of view and, in order to reach consensus, it is important to develop skills such as assuming a stance, justifying a point of view, counterarguing, negotiation, in order to attain social coexistence. Furthermore, argumentation develops critical thinking, since it promotes metacognitive processes that contribute to the construction of new knowledge.Despite its educational relevance, little is known about the performance of Peruvian students in terms of their capabilities. Therefore, it is pertinent to analyze the development of argumentative writing skills in these students, considering the socio-educational variables. To do this, it was analyzed 444 argumentative texts produced by 2nd-year of the middle-school students, who participated in the large-scale assessment implemented by the Ministry of Education from Peru.The results have shown that, in the process of justifying arguments, the majority of students adopted a clear and coherent position about a controversial issue (88 %), and justified it with at least two reasons main (69.5 %) establishing a logical connection between reasons and position (68 %). However, 52% of the students presented limitations to produce justifications that supported the main reason, since they were unable to develop it through subordinate reasons. Another result of the evaluation reveals a difficulty in the students to establish a dialogic argumentative structure that anticipated counterarguments or include contrary positions, as only 16 % developed this task. It has also been concluded that the socioeconomic variable predicts argumentative writing performance.